Analyses at the community, population, and individual levels for better understanding of South American Leaf Blight and of its etiological agent, Pseudocercospora ulei - Ferreira, Ana Francisca Tibúrcia Amorim Ferreira e (2018)
Pseudocercospora ulei causes the most devastating disease of the rubber tree (Hevea brasiliensis), South American leaf blight (SALB). Wild populations of H. brasiliensis from different river basins in the Amazon region have variable resistance levels to SALB, and the most resistant genotypes were found in the western Amazon, including the Brazilian state of Acre. Based on the premise that the plant microbiome can directly influence the plant-pathogen interactions and contribute to disease-resistance, we studied the endophytic microbiome of wild H. brasiliensis from three Amazonian states in Brazil. The diversity of fungal and prokaryotic endophytes was shaped by plant organ (leaf, sapwood or root) and there is strong evidence that the microbial communities from trees collected in Acre are markedly distinct and more diverse than those from the states of Amazonas and Pará. This pattern may be a function of geographic isolation influenced by differences in the geological history of eastern and western Amazon. Functional prediction revealed important roles of endophytes associated with disease suppressiveness, biological control, but also with pathogenesis. We also studied the allelic variation in five effector proteins genes conserved in Dothideomycetes between pathogen populations from Amazon region (AM) and commercial plantations located in the Northeast and Southeast regions in Brazil (N-AM). The analyzes showed the highest polymorphism in three effector genes (PuAve1, PuEcp2 and PuEcp6) and a pattern of division between groups of haplotypes of the AM and N-AM populations. The diversification in P. ulei effector genes is driven for intragenic recombination and selection, and two different mechanisms to avoid the recognition by rubber tree were detected in P. ulei populations. Characterization of melanin pigment with mass spectrometry (MALDI-TOF) and infrared (IR) have failed but revealed that data on beta-glucans have apparently been mistakenly assigned to melanin in recent reports in the literature. Using a specific inhibitor of melanization, we have found that the melanin present in P. ulei is made from1,8-dihydroxynaphthalene (1,8-DHN) and the genes involved in this biosynthetic pathway were mapped into the fungus genome. Taken together, our results provide new and important information about the microbial components (pathogen and whole microbiota) of the yet neglected SALB pathosystem.